Structure-Function Relationship of the Disintegrin Family: Sequence Signature and Integrin Interaction - Vasconcelos, Ariana A.; Estrada, Jorge C.; David, Victor; Wermelinger, Luciana S.; Almeida, Fabio C. L.; Zingali, Russolina B. (Frontiers in Molecular Biosciences, 2021)
Disintegrins are small cysteine-rich proteins found in a variety of snake venom. These proteins selectively modulate integrin function, heterodimeric receptors involved in cell-cell and cell-matrix interaction that are widely studied as therapeutic targets. Snake venom disintegrins emerged from the snake venom metalloproteinase and are classified according to the sequence size and number of disulfide bonds. Evolutive structure and function diversification of disintegrin family involves a stepwise decrease in the polypeptide chain, loss of cysteine residues, and selectivity. Since the structure elucidation of echistatin, the description of the structural properties of disintegrins has allowed the investigation of the mechanisms involved in integrin-cell-extracellular matrix interaction. This review provides an analysis of the structures of all family groups enabling the description of an expanded classification of the disintegrin family in 7 groups. Each group presents a particular disulfide pattern and sequence signatures, facilitating the identification of new disintegrins. The classification was based on the disintegrin-like domain of the human metalloproteinase (ADAM-10). We also present the sequence and structural signatures important for disintegrin-integrin interaction, unveiling the relationship between the structure and function of these proteins.